Paleomagnetic Constraint on the Carboniferous Paleoposition of Indochina and Its Implications for the Evolution of Eastern Paleo‐Tethys Ocean. Issue 7 (20th July 2020) - Yan, Yonggang; Duan, Lei; Liang, Shumin; Wang, Junhui; Huang, Baochun; Zheng, Wenjun; Zhang, Peizhen
Abstract: To better understand the rifting history and mechanism of the Indochina Block from eastern Gondwana, we report a paleomagnetic study on middle Carboniferous (~315 Ma) limestones from the southernmost Yunnan of China. Characteristic remanent magnetizations (ChRMs) were isolated from samples in 14 sites after secondary magnetizations were erased at relatively low temperature ranges, of which magnetites were interpreted to be the magnetic carriers for the former while goethites and pyrrhotites for the latter. The rock‐magnetically interpreted minerals are confirmed with a scanning electron microscope (SEM) on samples with a high concentration of magnetic minerals, of which the calcium carbonates were dissolved with a mixed solution of CH3 COOH and CH3 COONa. The ChRMs passed reversal and fold tests and are very likely a primary magnetization, which correspond a paleomagnetic pole of 76.1°S/181.3°E ( A 95  = 4.0°, N  = 14) and locate the Indochina Block at 18.4 ± 4.0°S. A relatively quiet tectonic period was suggested for the North Qiangtang, Indochina, and South China blocks during the middle Carboniferous‐early Permian, and a sequential start of rapid drifting of these blocks was recognized, which is coeval with the rifting of Cimmerian terranes from Gondwana. Key Points: The Indochina Block was located at 18.4 ± 4.0°S during the middle Carboniferous (~315 Ma) A quiet tectonic period during the middle Carboniferous‐early Permian is suggested for Indochina‐North Qiangtang‐South China The North Qiangtang, Indochina, and South China blocks started to rapid drifting sequentially from the earliest Permian to middle Triassic